Pengaruh Gender, Penghargaan Finansial, Pertimbangan Pasar Kerja, Personalitas dan Lingkungan Keluarga Terhadap Minat Berkarir Menjadi Akuntan Publik - Mega Rahmi; Yosep Eka Putra (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to examine the influence of gender, financial rewards, job market considerations, personality and family environment on interest in a career as a public accountant. The population of this study were students of the STIE KBP Padang Accounting Study Program. Sample selection used a purposive sampling method with a total of 178 respondents. The data used in this research is primary data and uses Structural Equation Modeling (SEM) analysis techniques with the help of SmartPLS version 4.0. The results of this research show that Gender, Financial Rewards, Job Market Considerations, Personality and Family Environment have a positive influence on interest in a career as a Public Accountant.